Perceptions of Football Analysts Goal-Scoring Opportunity Predictions: A Qualitative Case Study - Aguado-Méndez, Rubén D.; González-Jurado, José Antonio; Reina-Gómez, Álvaro; Otero-Saborido, Fernando Manuel (Frontiers in Psychology, 2021)
The study’s objective was to understand how tactical football analysts perceive general match analysis issues and to analyse their tactical interpretation of predictive models of conceded goal-scoring opportunities. Nine tactical analysts responded to semi-structured interviews that included a general section on match analysis and a specific one on the results of a study on goal-scoring opportunities conceded by a team of Spain’s La Liga. Following their transcription, the interviews were codified into categories by two researchers using Atlas Ti® software. Subsequently, a frequency count and co-occurrence analysis were performed based on the encodings. The content analysis reflected that analysts give a crucial role in the analysis of their own team and that of their opponent’s, the essential skills to exercise as a tactical analyst being “understanding of the game” and “clear observation methodology”. Based on the case study of the conceded goal-scoring opportunities, the major causes and/or solutions attributed by analysts to some of the predictive models of the case under study were the adaptability of the “style of play” itself according to the “opponent” and “pressure after losing”.